Calidad de las anotaciones de enfermería en centro quirúrgico del Hospital Regional Docente de Cajamarca. - Chaupe Sarzoza, Milagros Marilú (2019)
The present research work has the purpose of determining the level of quality of the nursing records recorded in the medical records of the patients of the Surgical Center service of the Regional Teaching Hospital of Cajamarca, during the months of October to December 2017. The The population is made up of 1557 medical records, being the sample of 97 medical records and the measuring instrument was applied to them. The procedures used were those provided by statistics, starting with the construction of tables, construction of graphs and the application of the statistical test of hypothesis testing to test the research hypothesis. The conclusion was that the quality level is good for nursing records at 83.5%, with 87.6% in the structure dimension and 79.4% in content dimension. It was concluded that the quality level of the nursing records is good and they are recorded in the medical records of the patients of the Surgical Center of the Regional Teaching Hospital of Cajamarca, during the months of October to December 2017.